Language Learning Strategies in Academic Writing: A Case Study of Indonesian Good Language Learners - Oktavianda, Melti (Jurnal Pendidikan Bahasa, 2024)
The theory of Language Learning Strategy (LLS) has been alluded to in many past works. This study examines the writing strategies employed by five high-achieving Indonesian bilingual university students in their academic essays. Writing at the university level is widely recognized as a challenging and complex process; therefore, this research seeks to identify similar and distinctive strategy use patterns among these bilingual students. Data were collected through semi-structured interviews adapted from Oxford’s (1990) language learning inventory and categorized into three writing stages: pre-writing, writing, and revising. The responses were transcribed and analyzed using directed content analysis to provide an in-depth understanding of the phenomenon. The findings revealed shared strategies in the Cognitive, Memory, Affective, and Compensation categories. However, significant differences were observed in Metacognitive and Social strategies highlighting the influence of individual preferences and cultural factors on academic writing practices.